Renal effects of the serine protease inhibitor aprotinin in healthy conscious mice - Woerner, Stefan; Bohnert, Bernhard N.; Woern, Matthias; Xiao, Mengyun; Janessa, Andrea; Birkenfeld, Andreas L.; Amann, Kerstin Ute; Daniel, Christoph; Artunc, Ferruh (Acta Pharmacologica Sinica, 2021)
Treatment with aprotinin, a broad-spectrum serine protease inhibitor with a molecular weight of 6512 Da, was associated with acute kidney injury, which was one of the reasons for withdrawal from the market in 2007. Inhibition of renal serine proteases regulating the epithelial sodium channel ENaC could be a possible mechanism. Herein, we studied the effect of aprotinin in wild-type 129S1/SvImJ mice on sodium handling, tubular function, and integrity under a control and low-salt diet. Mice were studied in metabolic cages, and aprotinin was delivered by subcutaneously implanted sustained release pellets (2 mg/day over 10 days). Mean urinary aprotinin concentration ranged between 642 ± 135 (day 2) and 127 ± 16 (day 8) µg/mL. Aprotinin caused impaired sodium preservation under a low-salt diet while stimulating excessive hyperaldosteronism and unexpectedly, proteolytic activation of ENaC. Aprotinin inhibited proximal tubular function leading to glucosuria and proteinuria. Plasma urea and cystatin C concentration increased significantly under aprotinin treatment. Kidney tissues from aprotinin-treated mice showed accumulation of intracellular aprotinin and expression of the kidney injury molecule 1 (KIM-1). In electron microscopy, electron-dense deposits were observed. There was no evidence for kidney injury in mice treated with a lower aprotinin dose (0.5 mg/day). In conclusion, high doses of aprotinin exert nephrotoxic effects by accumulation in the tubular system of healthy mice, leading to inhibition of proximal tubular function and counterregulatory stimulation of ENaC-mediated sodium transport.
CRIS-Team Scopus Importer:2021-04-09
Keywords: aprotinin; epithelial sodium channel; renal dysfunction; serine proteases; sodium